Multistation proprioceptive exercise program prevents ankle injuries in basketball - Eils, E. (Medicine & Science in Sports & Exercise, 2010)
Purpose: To investigate the effectiveness of a multistation proprioceptive exercise program for the prevention of ankle injuries in basketball players using a prospective randomized controlled trial in combination with biomechanical tests of neuromuscular performance.